Empathy and Phenomenology. Edith Stein’s Theory of Einfühlung - Mietelski, Tymoteusz (Bollettino Filosofico, 2022)
The main aim of this article is to present Stein’s theory of Einfühlung. The foundation of her philosophical thought was interest in human being. On Edmund Husserl’s lectures she often heard that an objective outer world could only be experienced intersubjectively by empathy. Stein defined empathy as a kind of acts in which one captures experiences of others. She meant that one can experience something that exists in another subject. In empathy the subject is not given experience from its source; there are two subjects taking part in that experience. Unlike in other conscious acts, here subjects are completely different from each other; they are not bound by identity-consciousness or continuity of experience. In that experience also human body plays an important role. Keywords: Another Subject, Cognition, Empathy, Human Being, Intersubjectivity, Phenomenology